2019
DOI: 10.1177/0894439319865903
|View full text |Cite
|
Sign up to set email alerts
|

Internet and Online Governmental Services Use Divide: Evidence From Oman

Abstract: Based on a sample of 21,546 individuals and 5,224 households, we use multilevel probit models to analyze the divides in the use of the Internet and online governmental services in Oman. We also study the main self-reported reasons for not using the Internet. The results reveal that characteristics such as education, employment status, nationality, role in the household, or age influence the likelihood of using both the Internet and online governmental services. Gender is only a relevant explanatory variable in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…For example, Hargittai and Dobransky (2017) found that Web use skills of older adults are positively related to number of their capital-enhancing activities on the internet. Therefore, having better skills may ensure their greater involvement in the online sphere including targeted e-government use (Martins and Al-Shekaili, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Hargittai and Dobransky (2017) found that Web use skills of older adults are positively related to number of their capital-enhancing activities on the internet. Therefore, having better skills may ensure their greater involvement in the online sphere including targeted e-government use (Martins and Al-Shekaili, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The popularization of broadband has gradually eliminated the ‘access divide’, but the ‘use divide’ caused by differences in internet application capabilities still plagues rural residents and has become a potential cause of the existence of the third-level digital divide. Generally, the higher the education level of an individual, the stronger the ability to use the internet (Martins and Al-Shekaili, 2021). Therefore, we construct Edu*Treated*Post to analyse whether raising the education level of residents can help reduce the urban–rural income gap arising from the expansion of ICC.…”
Section: Further Discussionmentioning
confidence: 99%
“…Rossember (2019) examined the interactive effects of ethnicity and trust in government on e-government engagement in Israel, documenting that using the Internet daily increases e-government use. Martins and Al-Shekaili (2021) studied the disparities of e-government engagement in Oman. Based on a nationally representative sample of users and households, they found that factors such as education, employment status, age, and digital skills (the stronger predictor) increase the chances to the use of online governmental services.…”
Section: E-government Disparities and Outcomesmentioning
confidence: 99%